Cordierite-based catalyst, method of preparation and use
Patent Information
- Application Number
- CN202610871524.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-16
- Publication Date
- 2026-10-30
AI Technical Summary
1、界面结合力弱:涂层与惰性堇青石载体之间多为物理附着或弱化学作用,在高温热震、气流冲刷及振动工况下易粉化、剥落,导致活性组分流失和催化剂失活
(1)本发明通过“机械化学活化预处理—堇青石载体表面纳米结构化处理—界面耦合剂辅助原位水热晶化—程序控温煅烧”的连续协同工艺,在堇青石载体表面原位构筑出具有明确分工的梯度功能涂层。高能球磨机械化学活化使活性组分前驱体、助剂前驱体及载体氧化物粉体在固相条件下实现纳米级均匀混合,并诱导形成高分散活性中间体,为后续元素的分步迁移和分层富集提供了物质基础;酸刻蚀及Si/Al纳米过渡层处理则显著提高了堇青石表面的羟基密度、比表面积及界面活性位点数量,为后续涂层的稳定附着和原位生长提供了必要条件;在此基础上,界面耦合剂在水热/蒸汽条件下充分水解并与载体表面羟基及过渡层发生缩合反应,促使涂层由传统的物理附着方式转变为以化学键连接为主的界面结合方式;随后再借助程序控温煅烧过程中不同元素氧化物在晶化速率、迁移能力、表面能及与载体亲和力方面的差异,引导TiO2/SiO2及La、Y等助剂优先向内层富集,V、Ce、Mn等活性组分优先分布于中层,而WO3/MoO3及疏水硅物种则在后期向外层偏聚,最终形成“内层强结合—中层高活性—外层抗中毒”的结构—功能一体化涂层。由此,本发明实质上解决了传统堇青石涂覆催化剂中“界面结合弱、涂层功能单一、活性组分分散不均、抗中毒能力不足”这几个问题难以兼顾的技术矛盾。
Smart Images

Figure CN122999173A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmental catalytic materials and chemical process technology, and particularly to cordierite-based catalysts, their preparation methods, and applications. Background Technology
[0002] Selective catalytic reduction (SCR) technology is used to remove nitrogen oxides (NOx) from industrial flue gas. x The mainstream technology for SCR catalysts is cordierite (2MgO·2Al2O3·5SiO2) honeycomb ceramics. Due to its excellent thermal stability, low coefficient of thermal expansion, and unique pore structure, it has become an ideal support for SCR catalysts. Traditional processes typically employ "wet impregnation-calcination" or "slurry coating-drying" methods to load active components (such as V2O5-WO3 / TiO2) onto the cordierite surface.
[0003] However, existing technologies have several bottlenecks: 1. Weak interfacial bonding: The coating and the inert cordierite carrier are mostly physically attached or weakly chemically bonded. Under high temperature thermal shock, airflow erosion and vibration conditions, it is easy to pulverize and peel off, resulting in loss of active components and deactivation of catalyst.
[0004] 2. Simple active layer structure: Traditional coatings are mostly homogeneous loading layers. The active components, additives and binders lack orderly distribution in the coating, making it difficult to simultaneously achieve interfacial bonding, low-temperature denitrification activity and resistance to SO2 and alkali metal poisoning.
[0005] 3. Uneven dispersion of active components: Wet mixing can easily lead to the agglomeration of active component precursors, which form large particles after calcination, reducing the density and utilization rate of active sites.
[0006] 4. Insufficient process synergy: Existing slurry coating, impregnation loading, coupling modification or sol-bonding processes mostly improve single problems, and usually cannot simultaneously solve the problems of weak bonding between the coating and cordierite carrier, easy agglomeration of active components, easy collapse of pore structure and easy entry of poisoned components into the active layer.
[0007] Existing technologies have disclosed various methods for preparing cordierite honeycomb ceramic support catalysts through coating or impregnation processes, but they are essentially still traditional physical mixing and coating, or although coupling modification is introduced, it is limited to monolayer chemical anchoring. None of these methods can fundamentally solve the problems of low coating-support interface bonding strength and single functional structure inside the coating.
[0008] Therefore, developing an innovative coating process that can achieve a strong bond between the coating and the support, construct an internal gradient functional structure, and balance high catalytic activity with strong resistance to poisoning is of great significance for promoting the industrial application of high-performance SCR catalysts. Summary of the Invention
[0009] Based on the technical problems existing in the background technology, this invention proposes cordierite-based catalysts, preparation methods and applications, and obtains high-performance catalysts with strong interfacial bonding and integrated structure and function.
[0010] The present invention proposes a method for preparing a cordierite-based catalyst, the method steps of which are as follows: S1: The active component precursor, auxiliary agent precursor, carrier oxide powder, structure directing agent and binder precursor are dry-mixed and then ball-milled to obtain activated powder; S2: Disperse the activated powder in an aqueous solution containing an interfacial coupling agent and a viscosity modifier to obtain a uniform slurry; S3: Acid etching is performed on the cordierite carrier, followed by coating with sol and then low-temperature calcination; S4: The carrier after low-temperature calcination is impregnated in slurry, and then subjected to low-temperature hydrothermal or steam treatment and programmed temperature-controlled calcination to obtain cordierite-based catalyst.
[0011] Preferably, the active component precursor in S1 is one or more of ammonium metavanadate, vanadium oxynitrate, cerium nitrate, and manganese nitrate; And / or, the auxiliary precursor is one or more of ammonium metatungstate, ammonium molybdate, ammonium dihydrogen phosphate, lanthanum nitrate and yttrium nitrate; And / or, the carrier oxide powder is one or more of anatase nano-titanium dioxide, silicon dioxide and zirconium dioxide; And / or, the structure directing agent is one or more of block copolymer P123, block copolymer F127 and carbon microspheres; And / or, the binder precursor is one or more of silica sol, aluminum sol and titanium sol.
[0012] Preferably, the mass ratio of the active component precursor, auxiliary agent precursor, carrier oxide powder, structure directing agent and binder precursor in S1 is (0.5-5):(2-15):(65-96):(0.5-5):(1-10), and the mass of the active component precursor, auxiliary agent precursor and binder precursor is based on the corresponding oxide.
[0013] Preferably, the ball milling conditions in S1 are: rotation speed 5000-30000 rpm, time 1-5 h.
[0014] Preferably, the interfacial coupling agent in S2 is one or more of the following: silane coupling agent KH-550, silane coupling agent KH-560, and aluminate coupling agent DL-411. And / or, the amount of interfacial coupling agent added is 0.5-3.0 wt% of the total solids mass of the slurry; And / or, the viscosity modifier is one or more of hydroxypropyl methylcellulose, polyethylene glycol and sodium polyacrylate; And / or, the amount of viscosity modifier added is 0.1-1.0 wt% of the total mass of the slurry; And / or, the slurry has a solid content of 30-50 wt%, a pH value of 3.0-5.0, and a viscosity of 2000-5000 cp.
[0015] Preferably, the acid solution used for acid etching of the cordierite carrier in S3 is a 3-10 wt% oxalic acid, citric acid, or nitric acid solution, the etching temperature is 40-80℃, and the etching time is 0.5-3h. And / or, the sol is a silica sol, an aluminum sol, or a silica-alumina composite sol. Preferably, the low-temperature calcination temperature in S3 is 300-500℃, and the time is 1-3h.
[0016] Preferably, the conditions for low-temperature hydrothermal or steam treatment in S4 are: temperature 80-150℃, pressure 0.1-0.5MPa, and treatment time 2-12h; And / or, the conditions for programmed temperature-controlled calcination are: in an air atmosphere, the temperature is increased from room temperature to 250-350℃ at a rate of 1-3℃ / min and held for 0.5-2h, then increased to 450-600℃ at a rate of 0.5-2℃ / min and held for 4-8h.
[0017] The cordierite-based catalyst proposed in this invention is prepared by the above-described preparation method.
[0018] The present invention proposes the application of the cordierite-based catalyst described above in denitrification.
[0019] Beneficial technical effects of the present invention: (1) This invention constructs a gradient functional coating with a clear division of labor on the surface of a cordierite carrier in situ through a continuous synergistic process of "mechanical and chemical activation pretreatment - nanostructuring treatment of cordierite carrier surface - in-situ hydrothermal crystallization assisted by interfacial coupling agent - programmed temperature controlled calcination". High-energy ball milling mechanical and chemical activation enables the active component precursor, auxiliary agent precursor and carrier oxide powder to achieve nanoscale uniform mixing under solid-phase conditions, and induces the formation of highly dispersed active intermediates, providing a material basis for the stepwise migration and layered enrichment of subsequent elements; acid etching and Si / Al nano-transition layer treatment significantly improve the hydroxyl density, specific surface area and number of interfacial active sites on the cordierite surface, providing the necessary conditions for the stable adhesion and in-situ growth of the subsequent coating; on this basis, the interfacial coupling agent is fully hydrolyzed under hydrothermal / steam conditions and reacts with the hydroxyl groups and transition layer on the carrier surface. The condensation reaction transforms the coating from a traditional physical adhesion method to an interfacial bonding method primarily based on chemical bonds. Subsequently, by leveraging the differences in crystallization rate, migration ability, surface energy, and affinity for the carrier among different elemental oxides during programmed temperature-controlled calcination, TiO2 / SiO2 and additives such as La and Y preferentially accumulate in the inner layer, while active components such as V, Ce, and Mn preferentially distribute in the middle layer. WO3 / MoO3 and hydrophobic silicon species then segregate towards the outer layer in the later stages, ultimately forming a structurally and functionally integrated coating characterized by "strong inner layer bonding—high middle layer activity—outer layer anti-poisoning." Thus, this invention substantially solves the technical contradiction of traditional cordierite-coated catalysts, which struggle to simultaneously address issues such as "weak interfacial bonding, single coating function, uneven dispersion of active components, and insufficient anti-poisoning ability."
[0020] (2) This invention significantly enhances the interfacial bonding strength between the coating and the cordierite support through a synergistic design of "surface nanostructuring treatment + interfacial coupling agent-assisted in-situ hydrothermal crystallization," thereby improving the mechanical stability, thermal shock resistance, and long-term service life of the catalyst. This is because acid etching and the Si / Al transition layer not only increase surface roughness and the number of anchoring points but also create a more suitable chemical environment for condensation reactions on the support surface. Under hydrothermal conditions, the interfacial coupling agent can expand from point-like anchoring to a planar connection network, forming a multi-level stable connection structure between the support, transition layer, interfacial coupling agent, and functional coating. This invention, through multi-step synergistic construction, creates a strong and tough bonding interface supported by chemical bonds and a stable interfacial structure, making the coating less prone to peeling and failure under scouring, vibration, and thermal fluctuation conditions.
[0021] (3) This invention achieves a gradient structure design with clear functional partitions in the cordierite-supported catalyst through a specific continuous process, so that the coating is no longer a traditional homogeneous coating, but a synergistic protection system with "outer layer protection - middle layer catalysis - inner layer capture". The WO3 / MoO3 and hydrophobic silica species enriched in the outer layer can inhibit SO2 adsorption and further oxidation, reduce the formation of sulfate on the outer and middle layers, and at the same time, rely on the small pore size and relatively stable surface chemical properties to form diffusion hindrance and steric hindrance for poisons such as KCl aerosol; the middle layer is enriched with highly dispersed active components to bear the NO x The main reaction tasks include reduction and CO / CH oxidation; the inner layer relies on the TiO2 / SiO2 framework with chemical properties similar to the carrier and the alkaline sites formed by La, Y and other auxiliary agents to further capture and fix the small amount of poison that penetrates the outer layer, thereby reducing its erosion and damage to the active sites in the middle layer.
[0022] (4) Based on the above-mentioned gradient functional structure, the catalyst prepared by this invention exhibits excellent resistance to sulfur and alkali metal poisoning. The underlying reason is that: the outer WO3 / MoO3 has low activity for further oxidation of SO2, which can inhibit the formation of SO3 and sulfate at the source; the hydrophobic SiO2 and the smaller pore size structure increase the resistance to the diffusion of SO2, water vapor and alkali metal aerosol into the interior; the inner La and other promoters have a stronger affinity for poisons that penetrate into the deeper layers, which can preferentially fix them and reduce the probability of poisons directly acting on active centers such as V and W.
[0023] (5) This invention achieves a high degree of optimization of active sites through the synergistic effect of mechanochemical activation, structure guidance and programmed calcination, thereby improving the intrinsic activity of the catalyst and the utilization rate of effective active sites. First, mechanochemical activation enables the active precursor and auxiliary precursor to be uniformly dispersed at the nanoscale, which reduces the agglomeration phenomenon that is prone to occur in traditional wet mixing and is conducive to the formation of more usable surface active centers. Second, the presence of structure guiding agents and in-situ hydrolysis / preliminary crystallization during hydrothermal treatment help to construct rich mesoporous structures, improve the diffusion efficiency of reactants in the coating, and reduce mass transfer resistance. Third, programmed temperature-controlled calcination avoids pore collapse, internal stress concentration and abnormal agglomeration of active components caused by single-stage rapid calcination, so that different functional components can complete stepwise crystallization, anchoring and segregation in a more suitable temperature range, thereby making the main catalytic active centers more distributed in the middle layer effective reaction region, rather than being buried in inefficient positions or transformed into low-activity phases at high temperatures.
[0024] (6) The mechanochemical activation step of the present invention is mainly based on solid phase pretreatment, which can reduce solvent consumption in traditional liquid phase processes; the introduction of hydrothermal treatment and programmed calcination makes the coating formation process more controllable, the process repeatability better, and has good industrial application prospects. Attached Figure Description
[0025] Figure 1 The images show cross-sectional SEM images of the catalyst prepared in Example 1 of this invention at different sizes; where (a) is 500 nm and (b) is 2 μm. Detailed Implementation
[0026] The present invention will be further explained below with reference to specific embodiments.
[0027] Example 1 Ammonium metavanadate (1.5 wt% V₂O₅), ammonium metatungstate (8 wt% WO₃), nano-anatase TiO₂ powder (average particle size 30 nm), lanthanum nitrate (2 wt% La₂O₃), block copolymer P123 (2 wt%), and silica sol (SiO₂, accounting for 5 wt% of the coating) were dry-mixed in proportion. In a high-energy planetary ball mill, using zirconia balls as grinding balls at a ball-to-material ratio of 10:1, the mixture was first mixed at 500 rpm for 30 minutes, and then activated at 15000 rpm for 2 hours.
[0028] The activated powder was added to an aqueous solution containing KH-550 silane coupling agent (1 wt% of the total solids of the slurry) and hydroxypropyl methylcellulose (0.5 wt% of the total solids of the slurry), and dispersed by high-speed shearing. The pH was adjusted to 4.0 to obtain slurry A with a solids content of 40%.
[0029] Cordierite carrier (200 mesh) was soaked in 5% oxalic acid solution at 60°C for 1 hour, washed with water and dried. It was then immersed in silica sol (10wt%), coated once with a dip coating, dried at 150°C and calcined at 400°C for 1 hour to obtain a carrier with a rough nano-SiO2 layer on the surface.
[0030] A support with a roughened nano-SiO2 layer on its surface was immersed in slurry A and vacuum-assisted impregnation for 5 minutes, followed by pulling at a constant speed. The wet preform was placed in an autoclave and treated with steam at 110°C for 6 hours. Subsequently, it was calcined in a muffle furnace: the temperature was increased to 300°C at 2°C / min and held for 1 hour, then increased to 500°C at 1°C / min and held for 4 hours to obtain the catalyst, denoted as Cat-1.
[0031] Figure 1 The cross-sectional SEM image of Cat-1 shows that there are no structural defects such as cracks or micropores inside the coating, and there is no local peeling or powdering of the coating. This indicates that after mechanochemical activation, hydrothermal crystallization and programmed temperature-controlled calcination, the catalyst coating has formed a dense and highly intact microstructure, which provides a good microstructure basis for its mechanical stability and catalytic performance.
[0032] Example 2 Ammonium metavanadate (0.5 wt% V₂O₅), ammonium metatungstate (1.6 wt% WO₃), nano-anatase TiO₂ powder (average particle size 30 nm), lanthanum nitrate (0.4 wt% La₂O₃), block copolymer P123 (0.5 wt%), and silica sol (SiO₂, accounting for 1 wt% of the coating) were dry-mixed in a specific ratio. Zirconia balls were used as grinding balls in a high-energy planetary ball mill at a ball-to-material ratio of 10:1. The mixture was first stirred at 500 rpm for 30 minutes, followed by activation at 15000 rpm for 2 hours.
[0033] The activated powder was added to an aqueous solution containing KH-550 silane coupling agent (1 wt% of the total solids of the slurry) and hydroxypropyl methylcellulose (0.5 wt% of the total solids of the slurry), and dispersed by high-speed shearing. The pH was adjusted to 4.0 to obtain slurry B with a solids content of 40%.
[0034] Cordierite carrier (200 mesh) was soaked in 5% oxalic acid solution at 60°C for 1 hour, washed with water and dried. It was then immersed in silica sol (10wt%), coated once with a dip coating, dried at 150°C and calcined at 400°C for 1 hour to obtain a carrier with a rough nano-SiO2 layer on the surface.
[0035] A carrier with a roughened nano-SiO2 layer on its surface was immersed in slurry B and vacuum-assisted impregnation for 5 minutes, followed by pulling at a constant speed. The wet preform was placed in an autoclave and treated with steam at 110°C for 6 hours. Subsequently, it was calcined in a muffle furnace: the temperature was increased to 300°C at 2°C / min and held for 1 hour, then increased to 500°C at 1°C / min and held for 4 hours to obtain the catalyst, designated Cat-2.
[0036] Example 3 Ammonium metavanadate (5 wt% V₂O₅), ammonium metatungstate (12 wt% WO₃), nano-anatase TiO₂ powder (average particle size 30 nm), lanthanum nitrate (3 wt% La₂O₃), block copolymer P123 (5 wt%), and silica sol (SiO₂, accounting for 10 wt% of the coating) were dry-mixed in proportion. In a high-energy planetary ball mill, using zirconia balls as grinding balls at a ball-to-material ratio of 10:1, the mixture was first mixed at 500 rpm for 30 minutes, and then activated at 15000 rpm for 2 hours.
[0037] The activated powder was added to an aqueous solution containing KH-550 silane coupling agent (1 wt% of the total solids of the slurry) and hydroxypropyl methylcellulose (0.5 wt% of the total solids of the slurry), and dispersed by high-speed shearing. The pH was adjusted to 4.0 to obtain slurry C with a solids content of 40%.
[0038] Cordierite carrier (200 mesh) was soaked in 5% oxalic acid solution at 60°C for 1 hour, washed with water and dried. It was then immersed in silica sol (10wt%), coated once with a dip coating, dried at 150°C and calcined at 400°C for 1 hour to obtain a carrier with a rough nano-SiO2 layer on the surface.
[0039] A support with a roughened nano-SiO2 layer on its surface was immersed in slurry C and vacuum-assisted impregnation for 5 minutes, followed by pulling at a constant speed. The wet preform was placed in an autoclave and treated with steam at 110°C for 6 hours. Subsequently, it was calcined in a muffle furnace: the temperature was increased to 300°C at 2°C / min and held for 1 hour, then increased to 500°C at 1°C / min and held for 4 hours to obtain the catalyst, designated Cat-3.
[0040] Comparative Example 1 Ammonium metavanadate (1.5wt% V2O5), ammonium metatungstate (8wt% WO3), nano-anatase TiO2 powder (average particle size 30nm), lanthanum nitrate (2wt% La2O3), block copolymer P123 (2wt%), and silica sol (SiO2, accounting for 5wt% of the coating) were directly added to an aqueous solution containing KH-550 silane coupling agent (accounting for 1wt% of the total solid mass of the slurry) and hydroxypropyl methylcellulose (accounting for 0.5wt% of the total slurry mass). The mixture was dispersed by high-speed shearing, and the pH was adjusted to 4.0 to obtain a slurry with a solid content of 40%. After coating, the temperature was directly increased to 500℃ at 1℃ / min and kept for 4h to obtain the catalyst, which was designated as Ref-1.
[0041] Comparative Example 2 The support with a roughened nano-SiO2 layer on its surface, prepared in Example 1, was immersed in slurry A and vacuum-assisted impregnation for 5 minutes, followed by pulling at a constant speed. The wet preform was placed in a muffle furnace for calcination: the temperature was increased to 300°C at 2°C / min and held for 1 hour, then increased to 500°C at 1°C / min and held for 4 hours to obtain the catalyst, denoted as Ref-2.
[0042] Comparative Example 3 Ammonium metavanadate (1.5 wt% V2O5), ammonium metatungstate (8 wt% WO3), nano-anatase TiO2 powder (average particle size 30 nm), lanthanum nitrate (2 wt% La2O3), block copolymer P123 (2 wt%), and silica sol (SiO2, accounting for 5 wt% of the coating) were directly added to an aqueous solution containing KH-550 silane coupling agent (accounting for 1 wt% of the total solid mass of the slurry) and hydroxypropyl methylcellulose (accounting for 0.5 wt% of the total solid mass of the slurry). The mixture was dispersed by high-speed shearing, and the pH was adjusted to 4.0 to obtain a slurry with a solid content of 40%.
[0043] All other conditions were the same as in Example 1, and the resulting catalyst was designated Ref-3.
[0044] Comparative Example 4 The activated powder prepared in Example 1 was added to an aqueous solution containing hydroxypropyl methylcellulose (0.5 wt% of the total slurry mass), dispersed by high-speed shearing, and the pH was adjusted to 4.0 to obtain a slurry with a solid content of 40%.
[0045] All other conditions were the same as in Example 1, and the resulting catalyst was designated Ref-4.
[0046] Comparative Example 5 The cordierite carrier (200 mesh) was immersed in slurry A prepared in Example 1, and vacuum-assisted impregnation was performed for 5 minutes, followed by pulling at a constant speed. The wet preform was placed in an autoclave and treated with steam at 110°C for 6 hours. Subsequently, it was calcined in a muffle furnace: the temperature was increased to 300°C at 2°C / min and held for 1 hour, and then increased to 500°C at 1°C / min and held for 4 hours to obtain the catalyst, designated Ref-5.
[0047] Comparative Example 6 The calcination conditions in this scheme in the muffle furnace are as follows: the temperature is increased to 500℃ at a rate of 1℃ / min and held for 4 hours. All other conditions are the same as in Example 1. The resulting catalyst is designated as Ref-6.
[0048] The performance of the catalysts prepared in Example 1 and Comparative Examples 1-6 was determined.
[0049] 1. Adhesion test (ultrasonic method) The catalyst sample was placed in water and ultrasonically treated (power 500W) for 30 minutes. The coating mass loss rate was then measured, and the test results are shown in Table 1.
[0050] Table 1. Adhesion test results of catalyst samples As shown in Table 1, the catalyst Cat-1 prepared in Example 1 of this invention exhibits a coating mass loss rate of less than 1% after ultrasonic treatment at 500W for 30 minutes, significantly lower than that of the comparative examples. Specifically, Ref-1 shows a loss rate of approximately 15%, Ref-2 approximately 5%, Ref-3 approximately 10%, Ref-4 approximately 7%, Ref-5 approximately 12%, and Ref-6 approximately 8%. This result demonstrates that the present invention, through the synergistic effects of mechanochemical activation, surface nanostructuring treatment, interface coupling agent-assisted hydrothermal treatment, and programmed temperature-controlled calcination, significantly improves the bonding strength between the coating and the cordierite support, enabling the coating to maintain high integrity even under external impact and liquid-phase disturbance conditions. In contrast, the comparative samples using traditional processes or lacking any key step all showed varying degrees of coating detachment, indicating that the interface structure constructed in this invention can effectively improve the mechanical stability of the catalyst and provide reliable assurance for long-term use.
[0051] 2. Catalytic activity test In a fixed-bed reactor, simulated flue gas was prepared with 500 ppm NO, 500 ppm NH3, 5% O2, and N2 in equilibrium, at a space velocity of 30,000 h⁻¹. -1 The catalytic activity test results are shown in Table 2.
[0052] The denitrification efficiency is calculated using the formula: η(NO x )=(C1-C2) / C1×100%.
[0053] In the formula, C1 and C2 are NO x The concentrations at the inlet and outlet were obtained using a flue gas analyzer.
[0054] Table 2. Results of catalytic activity tests As can be seen from the experimental results in Table 2, the catalyst Cat-1 prepared in Example 1 of this invention exhibits a denitrification efficiency higher than 95% within the 200-400°C temperature window, and its activity temperature window is significantly wider than that of the comparative examples. Ref-1 achieves 90% efficiency above 250°C, Ref-2 >95% within the 225-350°C window, Ref-3 >90% within the 250-350°C window, Ref-4 >95% within the 250-300°C window, Ref-5 reaches 90% above 200°C, and Ref-6 achieves >90% denitrification efficiency within the 225-350°C window. These results demonstrate that this invention, through the synergistic effects of mechanochemical activation, surface nanostructuring treatment, interface coupling agent-assisted hydrothermal treatment, and programmed temperature-controlled calcination, successfully optimizes the dispersion state and distribution gradient of the active components, significantly broadening the catalyst's activity temperature window. In contrast, conventional processes or comparative samples lacking any key step all exhibit varying degrees of narrowing of the activity temperature window, indicating that the gradient functional coating constructed in this invention can effectively enhance the intrinsic activity of the catalyst, providing an excellent structural basis and catalytic performance for efficient denitrification.
[0055] 3. Anti-poisoning test 50 ppm SO2 and 5 ppm KCl aerosol were added to the above flue gas, and the catalyst was run continuously for 100 hours. The changes in the denitrification activity of the catalyst product over time are shown in Table 3.
[0056] The denitrification efficiency is calculated using the formula: η(NO x = (C3-C4) / C3×100%.
[0057] In the formula, C3 and C4 are NO x The concentrations at the inlet and outlet were obtained using a flue gas analyzer.
[0058] Table 3. Different products in simulated flue gas (containing SO2 and K) + Changes in denitrification activity over time As shown in Table 3, the denitrification efficiency of Cat-1 decreased slowly from 98% to 92%, while Ref-1 decreased sharply from 90% to 65%, Ref-2 from 97% to 85%, Ref-3 from 94% to 78%, Ref-4 from 95% to 77%, Ref-5 from 96% to 71%, and Ref-6 from 92% to 70%. This indicates that the catalyst product prepared in this invention has excellent anti-poisoning properties.
[0059] Although embodiments of this application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of this application. The scope of this application is defined by the appended claims and their equivalents, all of which should be included within the protection scope of this application.
Claims
1. A method for preparing a cordierite-based catalyst, characterized in that, The steps are as follows: S1: The active component precursor, auxiliary agent precursor, carrier oxide powder, structure directing agent and binder precursor are dry-mixed and then ball-milled to obtain activated powder; S2: Disperse the activated powder in an aqueous solution containing an interfacial coupling agent and a viscosity modifier to obtain a uniform slurry; S3: Acid etching is performed on the cordierite carrier, followed by coating with sol and then low-temperature calcination; S4: The carrier after low-temperature calcination is impregnated in slurry, and then subjected to low-temperature hydrothermal or steam treatment and programmed temperature-controlled calcination to obtain cordierite-based catalyst.
2. The method for preparing the cordierite-based catalyst according to claim 1, characterized in that, The active component precursor in S1 is one or more of ammonium metavanadate, vanadium oxynitrate, cerium nitrate and manganese nitrate. And / or, the auxiliary precursor is one or more of ammonium metatungstate, ammonium molybdate, ammonium dihydrogen phosphate, lanthanum nitrate and yttrium nitrate; And / or, the carrier oxide powder is one or more of anatase nano-titanium dioxide, silicon dioxide and zirconium dioxide; And / or, the structure directing agent is one or more of block copolymer P123, block copolymer F127 and carbon microspheres; And / or, the binder precursor is one or more of silica sol, aluminum sol and titanium sol.
3. The method for preparing the cordierite-based catalyst according to claim 1, characterized in that, The mass ratio of the active component precursor, auxiliary agent precursor, carrier oxide powder, structure directing agent and binder precursor in S1 is (0.5-5):(2-15):(65-96):(0.5-5):(1-10), and the mass of the active component precursor, auxiliary agent precursor and binder precursor is based on the corresponding oxide.
4. The method for preparing the cordierite-based catalyst according to claim 1, characterized in that, The conditions for ball milling in S1 are: rotation speed 5000-30000 rpm, time 1-5 h.
5. The method for preparing the cordierite-based catalyst according to claim 1, characterized in that, The interface coupling agent in S2 is one or more of the following: silane coupling agent KH-550, silane coupling agent KH-560, and aluminate coupling agent DL-411. And / or, the amount of interfacial coupling agent added accounts for 0.5-3.0 wt% of the total solids mass of the slurry; And / or, the viscosity modifier is one or more of hydroxypropyl methylcellulose, polyethylene glycol and sodium polyacrylate; And / or, the amount of viscosity modifier added is 0.1-1.0 wt% of the total mass of the slurry; And / or, the slurry has a solid content of 30-50 wt%, a pH value of 3.0-5.0, and a viscosity of 2000-5000 cp.
6. The method for preparing the cordierite-based catalyst according to claim 1, characterized in that, The acid solution used for acid etching of the cordierite carrier in S3 is oxalic acid, citric acid or nitric acid solution with a concentration of 3-10 wt%, the etching temperature is 40-80℃ and the etching time is 0.5-3h; And / or, the sol is a silica sol, an aluminum sol, or a silica-alumina composite sol.
7. The method for preparing the cordierite-based catalyst according to claim 1, characterized in that, The low-temperature calcination temperature of S3 is 300-500℃, and the time is 1-3h.
8. The method for preparing the cordierite-based catalyst according to claim 1, characterized in that, The conditions for low-temperature hydrothermal or steam treatment in S4 are: temperature 80-150℃, pressure 0.1-0.5MPa, and treatment time 2-12h. And / or, the conditions for programmed temperature-controlled calcination are: in an air atmosphere, the temperature is increased from room temperature to 250-350℃ at a rate of 1-3℃ / min and held for 0.5-2h, then increased to 450-600℃ at a rate of 0.5-2℃ / min and held for 4-8h.
9. A cordierite-based catalyst, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.
10. The application of the cordierite-based catalyst as described in claim 9 in denitrification.
